1999
DOI: 10.1111/j.1745-4565.1999.tb00251.x
|View full text |Cite
|
Sign up to set email alerts
|

INJURY AND SURVIVAL OF AEROMONAS HYDROPHILA 7965 AND YERSINIA ENTEROCOLITICA 9610 FROM HIGH HYDROSTATIC PRESSURE

Abstract: Responses of Aeromonas hydrophila 7965 and Yersinia enterocolitica 9610 to high hydrostatic pressure were investigated in microbiological media and meat. Cultures were pressurized from 51 to 304 megaPascals (MPa) for 15 min in 200 mM sodium phosphate buffer (pH 7.0), tryptic soy broth and radiation‐sterilized ground pork. Trends in pressure response were similar in all three pressure menstrua. A 7‐log10 CFU/g reduction of A. hydrophila in pork resulted from treatment of 253 MPa for 15 min. A 7‐log10 CFU/g redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Ellenberg and Hoover (1999) studied the response of A. hydrophila to high hydrostatic pressure (from 51 to 304 megaPascals; MPa) for 15 min. The results showed that the pathogen had the ability to repair or grow following pressure treatment in pork.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Ellenberg and Hoover (1999) studied the response of A. hydrophila to high hydrostatic pressure (from 51 to 304 megaPascals; MPa) for 15 min. The results showed that the pathogen had the ability to repair or grow following pressure treatment in pork.…”
Section: Prevention and Controlmentioning
confidence: 99%
“…Most of the common bacterial food-borne pathogens such as Campylobacter jejuni (2), Salmonella (3,4), Vibrio spp. (5), Escherichia coli O157:H7 (4,6), Yersinia enterocolitica (4,7), and Listeria monocytogenes (4)(5)(6)8) have been investigated in a variety of food systems and buffers, at various temperatures and for various pressureholding times. However, much fewer studies have been conducted on high-pressure inactivation of microorganisms, especially foodborne pathogens, than on thermal inactivation, especially in terms of predictive microbiology.…”
Section: Introductionmentioning
confidence: 99%
“…1995; Stewart et al. 1997; Ellenberg and Hoover 1999). Generally, the vegetative Gram‐positive organisms are more recalcitrant to pressure inactivation than Gram‐negative bacteria; however, HPP is effective at reducing or eliminating most vegetative forms of bacteria at pressures in the range of 300–800 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…It offers benefit over traditional thermally processed foods in that micro-organisms and detrimental enzymes can be inactivated by HPP without significant changes in the taste, texture, colour or nutritional value of the food (Shearer et al 2000). Most of the common bacterial food-borne pathogens, such as Salmonella, Vibrio spp., Escherichia coli O157:H7, Yersinia enterocolitica and Listeria monocytogenes, have been investigated in a variety of food systems and buffers, at various temperatures and for various pressure durations (Metrick et al 1989;Styles et al 1991;Patterson et al 1995;Stewart et al 1997;Ellenberg and Hoover 1999). Generally, the vegetative Gram-positive organisms are more recalcitrant to pressure inactivation than Gram-negative bacteria; however, HPP is effective at reducing or eliminating most vegetative forms of bacteria at pressures in the range of 300-800 MPa.…”
Section: Introductionmentioning
confidence: 99%